Optimizing power normalization for G.fast linear precoder by linear programming - Muller, Francisco C. B. F.; Chenguang Lu; Eriksson, Per-Erik; Host, Stefan; Klautau, Aldebaro (2014 IEEE International Conference on Communications (ICC), 2014)
The use of vectoring for crosstalk cancellation in the new ITU-T G.fast standard for next generation DSL systems becomes essential for efficient utilization of the extended bandwidth (up to 200 MHz). In VDSL2 (up to 30 MHz), a zero-forcing-based linear precoder is used in downstream which approaches single-line performance. However, at high frequencies, the linear precoder may amplify the signal power substantially since the crosstalk channel is much stronger than at lower frequencies. Performance could be significantly degraded by power normalization to keep the PSD below the mask. In this work, we extended a per-line power normalization scheme by linear programming (LP) optimization. By simulations using measured cable data it is shown how the LP-based scheme further improves the linear precoder and it is also capable of balancing the data rate between lines. Further, the simulations also show the non-linear Tomlinson-Harashima precoder performs better than the linear precoders.